2016
DOI: 10.1002/mren.201500060
|View full text |Cite
|
Sign up to set email alerts
|

Flash Latex Production in a Continuous Helical Photoreactor: Releasing the Brake Pedal on Acrylate Chain Radical Polymerization

Abstract: At the forefront is the radical chain polymerization, that represents 40% of all processes for the production of commercial polymers, including some of the most common plastics such as polystyrene, acrylic or vinyl polymers. It is of high interest that the propagation step governing the chain-growth may be very fast, given that the propagation rate coeffi cient ( k p ) is for most monomers in the range of 10 2 -10 4 L mol −1 s −1 . Nevertheless, the paradoxical observation is that polymer chemists have always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As shown in s). Our first study served to initially set up equipment and find optimal concentrations, irradiance, and flow rates [19]. For sake of simplicity, the process was developed to be almost complete (95 %) after one passage through the continuous minireactor, and to reach steady-state operation after only two residence times, limiting the portion of products being out of specification.…”
Section: A Review Of Key Parameters Causing Pluggingmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in s). Our first study served to initially set up equipment and find optimal concentrations, irradiance, and flow rates [19]. For sake of simplicity, the process was developed to be almost complete (95 %) after one passage through the continuous minireactor, and to reach steady-state operation after only two residence times, limiting the portion of products being out of specification.…”
Section: A Review Of Key Parameters Causing Pluggingmentioning
confidence: 99%
“…In a variant emulsion-type process, Seeberger showed that styrene continuous photopolymerization (≈ 20 % solids content) could result in full conversion with a shorter residence time of 36 s [18]. Recently, we reported the continuous photopolymerization of n-butyl acrylate (BA) miniemulsion (25 % solids content) in a compact helix minireactor prepared in poly(tetrafluoroethylene) (PTFE) coiled tubing, yielding 95% conversion after 27 s residence time [19].…”
Section: Introductionmentioning
confidence: 99%
“…6) made up of UV-transparent fluoropolymer tubing wrapped at a defined distance around a radiation source of low electrical power (e.g. "black light" fluorescent tube) and with flow rates usually > 1 mL min -1 [62]. However, a transfer from batch to continuous process mode is by no means trivial.…”
Section: Photoreactors and Continuous Flow Operationsmentioning
confidence: 99%
“…The inset shows a magnification of the helically coiled tubing constructed by winding a PTFE tubing (1.5 mm inner diameter) around a quartz cylinder. This figure has been reproduced from [62] with permission of the copyright owners.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation